Challenges of teaching chemistry in pandemic covid-19: advantages and limitations - Salinas, Vinicio (2023)
The covid-19 pandemic has significantly affected education worldwide, including chemistry education. The abrupt transition to online learning and the need to adapt to new ways of teaching have posed significant challenges. Therefore, it is important to conduct a literature review with the aim of analyzing the main challenges and measures adopted in Chemistry teaching in the context of the covid-19 pandemic, to identify the most effective practices to address these challenges and to develop strategies to support learning. The methodology maintained a qualitative approach, of descriptive type, constituting a bibliographic review, based on the hermeneutic and analytical-synthetic research methods, as well as on the content analysis technique, for which a total of 57 publications from databases such as Scopus, Dialnet, Latindex and Scielo were taken as a sample, compiling high impact articles in Spanish, English and Portuguese. The results show that the pandemic has boosted the implementation of innovative measures and strategies in chemistry teaching, although it has also revealed the limitations and challenges that must be overcome to ensure quality education in the future. These new approaches need to be further evaluated and improved to ensure their effectiveness and accessibility for all students.